Coated Cutting Tools

JP2024519948A5Pending Publication Date: 2025-04-03SANDVIK COROMANT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023572088
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-27
Filing Date
2022-05-25
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Existing coated cutting tools face issues with poor adhesion between very fine-grained Ti(C,N) and Al2O3 layers, leading to inadequate wear resistance, particularly in metal cutting applications.

Method used

A coated cutting tool design featuring a Ti(C,N) layer with a fine-grained B1 portion and a coarse-grained B1 portion, combined with an α-Al2O3 layer, where the deposition process is adjusted to enhance adhesion by forming a coarse-grained Ti(C,N) surface for improved bonding, and the layers are characterized by specific grain sizes and orientations using XRD and TKD techniques.

Benefits of technology

The improved adhesion and grain structure enhance the cutting tool's resistance to wear, particularly flank and crater wear, resulting in increased tool life and durability in metal cutting operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a cutting tool comprising a substrate at least partially coated with a coating, said substrate being a cemented carbide, cermet or ceramic substrate, said coating comprising a layer of Ti(C,N), a layer of Al2O3 and a bonding layer therebetween. The Ti(C,N) layer is composed of columnar grains, the average grain size D 422 is 25 to 50 nm, the Ti(C,N) layer includes a B1 portion adjacent to the bonding layer, and the average grain size of the Ti(C,N) grains in the B1 portion is 25 to 50 nm, and the average grain size of the Ti(C,N) grains in the entire Ti(C,N) layer is 25 to 50 nm. 422 The Ti(C,N) grains in the B1 portion of the Ti(C,N) layer have an average grain size of 130 nm to 300 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated cutting tool comprising a substrate and a coating, the coating being deposited by CVD and comprising a Ti(C,N)-layer and an α-Al2O3-layer. [Background technology]

[0002] In the metal cutting industry, coated cutting tools are well known in the art. CVD-coated cutting tools and PVD-coated cutting tools are the two most prevalent types of coated cutting tools. The advantage of these coatings is their high resistance to chemical and abrasive wear, which is important for achieving long tool life of coated cutting tools. CVD coatings including a layer of Ti(C,N) together with a layer of alumina are known to perform well in turning or milling steels, for example.

[0003] EP 2 791 387 A1 discloses a coated cutting tool with a fine-grained titanium carbonitride layer. The coating is advantageous in that it exhibits high resistance to flaking in turning and high-speed cutting of nodular cast iron. A columnar CVD TiCN layer with an average grain width of 0.05-0.4 μm is described.

[0004] Recent studies have shown that the combination of very fine-grained Ti(C,N) and Al2O3 layers can lead to poor adhesion between Ti(C,N) and Al2O3. It is interesting to address this challenge since very fine-grained Ti(C,N) has shown promising cutting tool properties.

[0005] It is an object of the present invention to provide a coated cutting tool for metal cutting having a high degree of adhesion of the layers of the coating. A further object is to provide a coated cutting tool having high resistance to wear, in particular high resistance to flaking during metal cutting. It is also an object of the present invention to provide a cutting tool having high resistance to crater wear in metal cutting of steels. Summary of the Invention

[0006] At least one of the above mentioned objects is achieved by a cutting tool according to claim 1. Preferred embodiments are disclosed in the dependent claims.

[0007] The present invention relates to a cutting tool comprising a substrate at least partially coated with a coating comprising a layer of Ti(C,N), a layer of Al2O3 and a bonding layer therebetween, wherein the Ti(C,N) layer has a thickness of 3-25 μm and is composed of columnar grains, and the average grain size D of the Ti(C,N) layer is 0.01 to 0.1 μm. 422 is 25-50 nm as measured by X-ray diffraction using CuKα radiation, and the grain size D 422 But Scherrer's formula: Calculated from the full width at half maximum (FWHM) of the (422) peak using TIFF2024519948000002.tif13170, where D 422 is the average grain size of Ti(C,N), K is the shape factor, set here to 0.9, λ is the wavelength of CuKα radiation, set here to 1.5405 Å, and B 422 is the FWHM value of the (422) reflection, θ is the Bragg angle, the Ti(C,N) layer includes a B1 portion adjacent to the bonding layer, and the average grain size of the Ti(C,N) grains in the B1 portion is the average grain size D 422 and in the B1 portion of the Ti(C,N) layer, the Ti(C,N) grains have an average grain size of 130 to 300 nm as measured by TKD (Transmission Kikuchi Diffraction) in an analysis area of ​​5 x 5 μm on a plane extending parallel to the substrate surface.

[0008] The present invention provides improved adhesion between the very fine-grained Ti(C,N) layer and the α-Al2O3 layer. This improved adhesion is achieved by modifying the deposition process conditions at the end of the Ti(C,N) deposition so that some of the fine Ti(C,N) grains are spread and a coarser-grained Ti(C,N) portion is formed. The process conditions are then modified again, this time to provide an optimal outer surface of the Ti(C,N) grains. In this way, an outermost surface of Ti(C,N) is formed that is similar to the outermost surface of the coarse-grained Ti(C,N) that is known to exhibit high adhesion to the α-Al2O3 layer via a tie layer. If the average grain size of the B1 portion is too small, the adhesion to the subsequently deposited α-Al2O3 layer is not improved. The average grain size of the B1 portion is preferably less than 300 nm, which is favorable for wear resistance.

[0009] Due to limited resolution, it is difficult to study the grain size of very fine-grained Ti(C,N) with SEM. Herein, the average grain size of the fine-grained part of the Ti(C,N) layer is instead specified by XRD and the Scherrer equation. The signal from XRD also contains information from the coarser-grained Ti(C,N)B1 part, but this contribution is believed to be limited.

[0010] On the other hand, investigating the grain size of the coarse-grained B1 part presented the challenge since it is only a small part of the Ti(C,N) layer and therefore a method with very high accuracy had to be chosen. Planar investigation by TKD was chosen since the information obtained contained both information about the grain size and also about the orientation of the Ti(C,N) grains on a very local scale.

[0011] In one embodiment of the present invention, the Ti(C,N) layer in the B1 portion of the Ti(C,N) layer exhibits an orientation when measured by TKD in a plane of the Ti(C,N) layer extending parallel to the substrate surface and when measured over an area of ​​at least 5×5 μm, the surface normal of the Ti(C,N) layer is parallel to the surface normal of the substrate surface, and ≧93%, preferably ≧95%, of the analyzed area is within 15 degrees of the surface normal of the Ti(C,N) layer. <211> Has direction.

[0012] closest to the bonding layer and therefore also closest to the α-Al2O3 layer, <211> A Ti(C,N) layer with a high degree of orientation along the 001 direction is believed to be advantageous in attempting to deposit a highly 001 oriented α-Al2O3 layer. Less than 93% of the analyzed area was within 15 degrees of the surface normal of the Ti(C,N) layer. <211> In the case of a 001 oriented crystal, the 001 orientation of the subsequent α-Al2O3 layer is less pronounced.

[0013] In one embodiment of the present invention, the thickness of the B1 portion of the Ti(C,N) layer is 0.5-1.5 μm, preferably 0.6-0.9 μm, most preferably 0.6-0.8 μm, measured in the growth direction of the coating.

[0014] Fine-grained Ti(C,N) is advantageous as a wear-resistant layer, which may be due to its large amount of grain boundaries or the smoother or more uniform thickness of the layer. Therefore, the portion of the TiCN layer that is fine-grained should be relatively thick. The portion of the coarse grains that contributes to increased adhesion is relatively limited, with the thickness of the B1 portion being preferably 0.5-1.5 μm, more preferably 0.6-0.9 μm, and most preferably 0.6-0.8 μm. If the B1 portion is too thin, adhesion will not be improved.

[0015] In one embodiment of the present invention, the tie layer comprises at least one compound selected from the group of titanium carboxide, titanium oxynitride, and titanium carboxynitride.

[0016] A titanium carboxylate, titanium oxynitride, or titanium carboxynitride tie layer is advantageous in that it can provide an epitaxial relationship between the Ti(C,N) layer and the α-Al2O3 layer.

[0017] In one embodiment of the present invention, the grain size D of Ti(C,N) 422 The thickness is 25 to 40 nm, preferably 25 to 35 nm.

[0018] The present invention, which improves adhesion between fine-grained Ti(C,N) and α-Al2O3 layers, is directed to Ti(C,N) layers having very fine grains, e.g. Ti(C,N) grain size D 422 It is particularly advantageous if the thickness is between 25 and 40 nm, or even between 25 and 35 nm.

[0019] In one embodiment of the present invention, the Ti(C,N) layer exhibits an X-ray diffraction pattern when measured using CuKα radiation and a θ-2θ scan, where TC(hkl) is determined according to the Harris equation: TIFF2024519948000003.tif22170, where I(hkl) is the measured intensity (integrated area) of the (hkl) reflection, I0(hkl) is the standard intensity according to ICDD PDF Card No. 42-1489, n is the number of reflections, and the reflections used in the calculation are (111), (200), (220), (311), (331), (420), and (422), and TC(422) is ≧3, preferably ≧4.

[0020] In one embodiment of the present invention, the Al2O3 layer is preferably an α-Al2O3 layer, the average thickness of the α-Al2O3 layer being 1 μm to 15 μm, preferably 3 to 10 μm.

[0021] In one embodiment of the invention, the α-Al2O3-layer exhibits a texture coefficient TC(hkl), as measured by X-ray diffraction using CuKα radiation and a θ-2θ scan, as defined by the Harris equation, where I(hkl) is the measured intensity (integrated area) of the (hkl) reflections, I0(hkl) is the standard intensity according to ICDD PDF Card No. 00-010-0173, n is the number of reflections used in the calculation, and the (hkl) reflections used are (104), (110), (113), (024), (116), (214), (300), and (0012), characterized in that TC(0012) is ≧7.5, preferably ≧7.7, more preferably ≧7.8.

[0022] In one embodiment of the invention, the layer, wherein said α-Al2O3 layer exhibits a TC(110) of ≦0.2, preferably ≦0.1.

[0023] In one embodiment of the present invention, the Ti(C,N) grains in the B1 part of the Ti(C,N) layer have an average grain size of 130 nm to 165 nm as measured by TKD on an analyzed area of ​​5 × 5 μm on a plane running parallel to the substrate surface. It was found that if the average grain size of the B1 part is too large, the highest orientation of the subsequently deposited α-Al2O3 layer cannot be reached, although the adhesion is still high.

[0024] In one embodiment of the invention, the α-Al2O3 layer of the O1 portion of the α-Al2O3 layer exhibits an orientation when measured by electron backscatter diffraction (EBSD) at a cross-section of the α-Al2O3 layer and when measured as an average over at least four different regions of an analyzed area of ​​at least 1 × 10 μm, the O1 portion extending 1 μm from the bonding layer, a surface normal of the α-Al2O3 layer is parallel to a surface normal of the substrate surface, and ≧80%, preferably ≧90%, more preferably ≧95%, and most preferably ≧97% of the analyzed area is within 15 degrees of the surface normal of the α-Al2O3 layer. <001> Has direction.

[0025] This high orientation of the α-Al2O3 layer in the O1 region, i.e. the region at the bottom of the α-Al2O3 layer adjacent to the bond layer, has been shown to be unexpectedly advantageous in contributing to improved resistance to first and second flank wear and also increased crater wear in turning of steel.

[0026] In one embodiment of the present invention, the average thickness of the Ti(C,N) layer is 4 to 20 μm, preferably 5 to 15 μm.

[0027] In one embodiment of the present invention, the average thickness of the bonding layer is 0.25 to 2.5 μm, preferably 0.5 to 2.0 μm.

[0028] In one embodiment of the present invention, the average thickness of the coating is 5.0 μm to 30.0 μm, preferably 10 to 20 μm.

[0029] In one embodiment of the invention, the substrate is a cemented carbide, cermet, or ceramic substrate.

[0030] The atomic ratio of carbon to the total of carbon and nitrogen contained in the Ti(C,N) layer of the present invention (C / (C+N)) is preferably 0.50 to 0.65, and more preferably 0.55 to 0.62, as measured by electron microprobe analysis.

[0031] Further and other objects and features of the present invention will become apparent from the following definitions and examples considered in conjunction with the accompanying drawings.

[0032] definition The term "cutting tool" is intended in this specification to denote a cutting tool suitable for metal cutting applications, such as an insert, an end mill or a drill. The application area may be, for example, turning, milling or drilling of metals such as steel.

[0033] method Average grain size of Ti(C,N) layer, D 422 To investigate the average grain size of the Ti(C,N) grains in the Ti(C,N) layer, X-ray diffraction (XRD) was performed on the flank face using a PANalytical CubiX3 diffractometer equipped with a PIXcel detector. The coated cutting tool was mounted on the sample holder to ensure that the flank face of the sample was parallel to the reference plane of the sample holder and furthermore that the flank face was at the appropriate height. Cu-Kα radiation was used for the measurements, with a voltage of 45 kV and a current of 40 mA. A 1 / 2 degree anti-scatter slit and a 1 / 4 degree divergence slit were used. The diffraction intensity from the coated cutting tool was measured over a 2θ range of 20°-140°, i.e., a range of 10-70° incidence angles θ. Data analysis, including background fitting of the data, Cu-Kα2 stripping, and profile fitting, was performed using PANalytical's X'Pert HighScore Plus software.

[0034] The full width at half maximum of the integrated peak of the profile fitted curve obtained from PANalytical's X'Pert HighScore Plus software was used to calculate the layer grain size by the Scherrer equation (Eq. 1) (Birkholz, 2006).

[0035] Average grain size D 422 is the Scherrer formula: Calculated from the full width at half maximum (FWHM) of the (422) peak using TIFF2024519948000004.tif11170, where D 422 is the average grain size of Ti(C,N), K is the shape factor, set here to 0.9, λ is the wavelength of CuKα1 radiation, set here to 1.5405 Å, and B 422 is the FWHM value of the (422) reflection, and θ is the Bragg angle, i.e., the angle of incidence.

[0036] The FWHM obtained from the measurements includes both instrumental broadening and broadening caused by small grain sizes. To compensate for this, a Gaussian approximation was used (Birkholz, 2006). 422is the linewidth broadening (in radians) at FWHM after subtracting the instrumental broadening (0.00174533 radians), and is given by Equation (2): B 422 =√((FWHM obs ) 2 -(FWHM ins ) 2 ) (2) wherein B 422 is the broadening (in radians) used in calculating grain size, and FWHM obs is the measured broadening (in radians) and FWHM ins is the instrumental broadening (in radians).

[0037] Possible further layers on top of the Ti(C,N) layer will affect the X-ray intensity entering the Ti(C,N) layer and exiting the entire coating, and corrections for these must be made taking into account the linear absorption coefficients of the respective compounds in the layers. Alternatively, further layers on top of the Ti(C,N) monolayer can be removed by methods that do not substantially affect the results of the XRD measurements, e.g. chemical etching.

[0038] Grain size and orientation of the B1 part of Ti(C,N). In the topmost region of the Ti(C,N) layer, region B1, which is located closest to the bonding layer that bonds the Al2O3 layer to the Ti(C,N) layer, the grains of Ti(C,N) are enlarged to improve adhesion. The average grain size of the Ti(C,N) grains in this region is analyzed through the plane of region B1, which runs in a plane parallel to the surface of the substrate, so that the width of the columnar grains can be examined without any obstruction, e.g., by overlapping grains.

[0039] Specimens for grain area analysis of the B1 region were prepared by producing planar thin foil specimens of the region of interest by FIB in-situ lift-out technique (Langford & Clinton, 2004). Samples were taken from polished cross sections. A Helios Nanolab 650 with a Ga+ ion source was used for sample preparation.

[0040] The area of ​​interest was marked on the edge with a cross etched into the surface using an ion current of 79 pA and an accelerating voltage of 30 kV to ensure that the exact area of ​​interest was at the center of the specimen. The area was then covered with a protective Pt layer approximately 2 μm thick, deposited using an ion current of 430 pA and an accelerating voltage of 30 kV. After protective Pt deposition, the sample was prepared using the well-known in-situ lift-out technique (Langford & Clinton, 2004).

[0041] Specimens were thinned to a thickness of <200 nm to ensure electron transparency.

[0042] The grain size of the B1 region was analyzed using transmission Kikuchi diffraction (TKD) on a Helios Nanolab 650 equipped with an Oxford symmetry EBSD detector. An accelerating voltage of 20 kV and a beam current of 13–26 nA were used. An area of ​​at least 5 × 5 μm (at least 640 grains) was analyzed with a step size of 10 nm and Speed ​​1 binning mode was used (622 × 512 pix). The average grain size (equivalent circle) was analyzed using the Aztec Crystal software package (v2.0) and for gentle noise reduction, one automated cleanup using the Aztec Crystal software (v2.0) was applied. The samples were analyzed with the specimen surface parallel to the substrate surface, thus ensuring that the out-of-plane orientation of the coating was parallel to the sample normal. The threshold for grain detection was set at 10° and an area of ​​at least 40 pixels.

[0043] The orientation is determined as the amount (%) of the analyzed area that is within a certain angular deviation from the set axis. In the B1 area, the orientation is parallel to the surface normal. <211> The Ti(C,N) direction was chosen. The orientation is <211> The orientation was calculated as the amount of analyzed area that deviated ≦15° from the Ti(C,N) direction. Aztec Crystal software (v2.0) was used to determine the orientation.

[0044] For the measurement of Ti(C,N), the reference pattern of Ti(C,N), J. Electrochem. Soc. [JESOAN], (1950), Vol. 97, pp. 299-304, was used, and 89 reflectors were used for the measurement.

[0045] Orientation of the bottom Al2O3-O1 part The part of the Al2O3 layer close to the bond layer is very highly oriented in the present invention. To analyze this region, a cross section of the coating was prepared and the Al2O3 grains in the O1 section, extending 1 μm in height from the bond layer, were examined in detail by EBSD. The polished cross section was prepared by mounting each of the CNMG120408-PM inserts in black conductive phenolic resin from AKASEL, which was then ground to about 1 mm, and then polished in two steps using a diamond slurry solution: coarse (9 μm) and fine (1 μm) polishing. A final polishing was performed using a colloidal silica solution.

[0046] The orientation of the bottom part of Al2O3 is determined as the amount (%) of the analyzed area that is within a certain angular deviation from the set axis. For the O1 part, the orientation is parallel to the surface normal. <001> The Al2O3 direction was chosen. The orientation is <001> It was calculated as the amount of analyzed area that had a deviation of ≦15° from the Al2O3 direction.

[0047] Areas of at least 80 μm width were analyzed with a step size of 50 nm and Speed ​​1 binning mode was used (622 × 512 pix). To analyze the orientation of O1, four rectangular shaped sections of O1 were randomly chosen with a size of 10 μm width and 1 μm height along the contact surface. The orientation was calculated as the average of the four rectangular shaped sections. One automatic cleanup step and one zero solution removal using five nearest neighbor levels were applied to the data. Aztec Crystal software (v2.0) was used to determine the orientation.

[0048] The orientation of the O1 moiety was analyzed using a Zeiss Supra 55 and a Helios Nanolab 650, both equipped with Oxford-symmetry EBSD detectors. An accelerating voltage of 20 kV and beam currents of 13–26 nA were used. The samples were mounted in a sample holder pretilted at 70° to ensure maximum collection efficiency.

[0049] For the measurements of Al2O3, a reference pattern of Alumina (Alpha), Acta Crystallogr, Sec B [ACBCAR], Vol. 49B, pp. 973-980, was used, and 89 reflectors were used in the measurements.

[0050] SEM Survey SEM examination of the polished cross-sections and top surfaces of the samples was performed with a Carl Zeiss AG-Supra 40 operated at an accelerating voltage of 3 kV and an aperture size of 30 μm. Images were acquired using a secondary electron detector.

[0051] X-ray diffraction measurements of Ti(C,N) and Al2O3 To investigate the structure throughout the layer, X-ray diffraction was performed on the flank face of the cutting tool insert using a PANalytical CubiX3 diffractometer equipped with a PIXcel detector. The coated cutting tool insert was mounted in a sample holder ensuring that the flank face of the cutting tool insert was parallel to the reference plane of the sample holder and furthermore that the flank face was at the appropriate height. Cu-Kα radiation was used for the measurements, the voltage was 45 kV and the current was 40 mA. 1 / 2 degree anti-scatter slits and 1 / 4 degree divergence slits were used. The diffraction intensity from the coated cutting tool was measured over a 2θ range of 20°-140°, i.e. over a range of incidence angles θ of 10-70°.

[0052] Background subtraction of data, Cu-K α2Stripping and data analysis, including profile fitting, were performed using PANalytical's X'Pert HighScore Plus software. A general description of the fitting is given below. The output from this program (integrated peak areas of the profile fitted curves) was then used to calculate the texture coefficients of the layers by comparing the ratio of the measured intensity data to the standard intensity data from the PDF card of a particular layer (e.g., Ti(C,N) or α-Al2O3 layers) using Harris' equation (3) disclosed below. Since the layers are of finite thickness, the relative intensity of a pair of peaks at different 2θ angles will be different from that for the bulk sample due to differences in path length through the layers. Therefore, when calculating the TC value, a thin film correction was applied to the extracted integrated peak area intensity of the profile fitted curve, taking into account the linear absorption coefficient of the layer as well. Since further layers that may be present, for example on top of the α-Al2O3 layer, will affect the X-ray intensity entering the α-Al2O3 layer and exiting the entire coating, corrections for these must also be made, taking into account the linear absorption coefficients of the respective compounds in the layer. The same applies to the X-ray diffraction measurement of the Ti(C,N) layer, if the Ti(C,N) layer is located, for example, below an α-Al2O3 layer. Alternatively, further layers on top of the alumina layer, for example TiN, can be removed by methods that do not substantially affect the results of the XRD measurement, for example chemical etching.

[0053] To investigate the structure of the α-Al2O3 layer, CuK α Radiation is used to perform X-ray diffraction, according to Harris' equation (3): Calculate the texture coefficient TC(hkl) for different growth directions of the columnar grains of the α-Al2O3 layer according to TIFF2024519948000005.tif14170, where I(hkl) = measured (integrated area) intensity of the (hkl) reflection, I0(hkl) = standard intensity according to ICDD PDF card number 00-010-0173, n = number of reflections used in the calculation. In this case, the (hkl) reflections used are (104), (110), (113), (024), (116), (214), (300), and (0012). The measured integrated peak areas are thin film corrected and corrected for any further layers above (i.e. on top of) the α-Al2O3 layer before calculating the ratio.

[0054] The texture coefficients TC(hkl) for different growth directions of columnar grains in Ti(C,N) layers were calculated by the previously disclosed Harris formula (3), where I(hkl) is the measured (integrated area) intensity of the (hkl) reflection, I0(hkl) is the standard intensity according to ICDD PDF card number 42-1489, and n is the number of reflections used in the calculation. In this case, the (hkl) reflections used are (111), (200), (220), (311), (331), (420), and (422).

[0055] It should be noted that overlapping of peaks is a possible phenomenon in X-ray diffraction analysis of coatings, for example comprising several crystalline layers and / or deposited on substrates comprising crystalline phases, which must be taken into account and compensated for. The overlapping of peaks from Ti(C,N) layers with peaks from α-Al2O3 layers can affect the measurements and must be taken into account. It should also be noted that, for example, WC in the substrate may have diffraction peaks close to the relevant peaks of the present invention.

[0056] Embodiments of the present invention will now be described with reference to the accompanying drawings. [Brief description of the drawings]

[0057] [Figure 1]FIG. 2 is a scanning electron microscope (SEM) image of a cross section of sample D, an example of a coating of the present invention, showing the B1 portion of the Ti(C,N) layer (1), the tie layer (2), and the O1 portion of the α-Al2O3 layer (3). [Diagram 2] Scanning electron microscope (SEM) image of a cross section of an example of a reference coating, sample A, showing the top Ti(C,N) (1), the tie layer (2), and the bottom α-Al2O3 (3). [Diagram 3] FIG. 2 is a scanning electron microscope (SEM) image of a cross section of sample G, an example of a coating of the present invention, showing the B1 portion of the Ti(C,N) layer (1), the tie layer (2), and the O1 portion of the α-Al2O3 layer (3). [Figure 4] Scanning electron microscope (SEM) image of a cross section of an example of a reference coating, sample B, showing the top Ti(C,N) (1), the bond layer (2), and the bottom α-Al2O3 (3). [Diagram 5] Scanning electron microscope (SEM) image of the top surface of part B1 of a sample with a Ti(C,N) layer corresponding to the Ti(C,N) of sample D, showing the morphology of the outermost surface of part B1. [Figure 6] Scanning electron microscope (SEM) image of the top surface of the Ti(C,N) layer of a sample with a Ti(C,N) layer equivalent to the Ti(C,N) of sample B, showing the very fine-grained Ti(C,N) outermost morphology. [Figure 7] Scanning electron microscope (SEM) image of the top surface of the Ti(C,N) layer of a specimen with a Ti(C,N) layer equivalent to the Ti(C,N) of reference specimen A, showing the outermost morphology of the coarse-grained Ti(C,N). [Figure 8] 1 is a schematic overview showing the location of the layers and parts of the present invention: the Ti(C,N) layer (1), the B1 part of the Ti(C,N) layer (1), the tie layer (2), the α-Al2O3 layer (3), the O1 part of the α-Al2O3 layer (3), and the substrate (4). [Figure 9] This is a band contrast TKD image of a plane of sample D, showing Ti(C,N) crystal grains in the B1 region. EXAMPLES

[0058] Exemplary embodiments of the present invention will now be disclosed in more detail and compared with a reference embodiment.Coated cutting tools (inserts) were manufactured, analyzed and tested in cutting tests.

[0059] The cemented carbide substrate was fabricated using conventional processes including milling, mixing, spray drying, pressing, and sintering. The ISO type shape of the cemented carbide substrate (insert) was CNMG-120408-PM. The composition of the cemented carbide was 7.2 wt% Co, 2.9 wt% TaC, 0.5 wt% NbC, 1.9 wt% TiC, 0.4 wt% TiN, and the balance was WC.

[0060] Prior to deposition of the coating, the substrate was subjected to a mild blasting treatment to remove any residues from the sintering process on the substrate surface.

[0061] CVD deposition The sintered substrates were CVD coated in an Ionbond size 530 radial CVD reactor capable of accommodating 10,000 cutting inserts of size 1 / 2 inch. Samples for further testing and analysis were selected from the center of the chamber along half the radius of the plate, at a location between the center and the periphery of the plate. A mass flow controller was selected to allow setting a high flow rate of, for example, CH3CN.

[0062] A first innermost coating of approximately 0.2 μm of TiN was deposited on all substrates in a process at 400 mbar and 885° C. A gas mixture of 48.8 vol % H2, 48.8 vol % N2, and 2.4 vol % TiCl4 was used.

[0063] Then, the Ti(C,N) layer was subsequently deposited and all samples A-G were deposited with different Ti(C,N) layers according to the following: Reference sample A was deposited with process steps V and W as shown in Table 1. The temperature adjustment from 885 °C to 870 °C before starting with process step X in samples B-G was performed at 80 mbar in 50 vol% H2 and 50 vol% N2. The Ti(C,N) layer of reference sample B was deposited with process step X as shown in Table 1. In samples C-G, the Ti(C,N) layer was deposited with process steps X, Y, and Z using the deposition times as shown in Tables 1 and 2. The process times were adjusted to reach approximately the same total thickness of the Ti(C,N) layer in all samples. TIFF2024519948000006.tif157170TIFF2024519948000007.tif89170

[0064] A 0.7-0.9 μm thick tie layer was deposited at 1000 °C on top of the Ti(C,N) layer by a process consisting of four separate reaction steps: an 8 min HTCVD Ti(C,N) step with TiCl4, CH4, N2, HCl, and H2 at 400 mbar, followed by a 7 min second step (Ti(C,N,O)-1) with TiCl4, CH3CN, CO, N2, and H2 at 70 mbar, followed by a 5 min third step (Ti(C,N,O)-2) with TiCl4, CH3CN, CO, N2, and H2 at 70 mbar, and finally a 6 min fourth step (TiN) with TiCl4, N2, and H2 at 70 mbar. During the third deposition step, the CO gas flow rate was continuously increased linearly from the start value to the stop value shown in Table 3. All other gas flow rates were kept constant, but as the total gas flow rate was increased, the concentrations of all gases were affected somewhat due to this. The bonded layer was oxidized in a mixture of CO2, CO, N2, and H2 for 4 min before the subsequent Al2O3 nucleation was initiated.

[0065] The deposition details of the tie layer are given in Table 3. TIFF2024519948000008.tif123170

[0066] An α-Al2O3 layer was deposited on top of the bond layer. All α-Al2O3 layers were deposited in two steps at 1000° C. and 55 mbar. The first step used 1.2 vol% AlCl3, 4.7 vol% CO2, 1.8 vol% HCl, and balance H2 to produce an α-Al2O3 thickness of about 0.1 μm, and the second step is disclosed below and produces an α-Al2O3 layer total thickness of about 5 μm. The second step of the α-Al2O3 layer was deposited using 1.16% AlCl3, 4.65% CO2, 2.91% HCl, 0.58% H2S, and balance H2.

[0067] Coverage Analysis The layer thickness was measured on the rake face of the cutting tool samples using a scanning electron microscope. The layer thicknesses of the coatings for samples A-G are shown in Table 4. TIFF2024519948000009.tif110170

[0068] The grain size of the Ti(C,N) layer was analyzed both as the average value for the whole Ti(C,N) layer and for the B1 part close to the bonding layer. The results are shown in Table 5.

[0069] The orientation of Ti(C,N) crystal grains in the B1 portion of the Ti(C,N) layer and the orientation of α-Al2O3 crystal grains in the O1 portion of the α-Al2O3 layer were analyzed. The results are shown in Table 5.

[0070] The grain size of the Ti(C,N) layer of reference sample A is too large to be analyzed by XRD and the Scherrer equation is not considered valid for grain sizes larger than about 0.2 μm. The average grain size of this layer is larger than 200 nm as measured by cross-sectional SEM images. TIFF2024519948000010.tif114170

[0071] The texture coefficients of Ti(C,N) and α-Al2O3 layers were analyzed using X-ray diffraction, and the results are shown in Tables 6 and 7. TIFF2024519948000011.tif105170TIFF2024519948000012.tif84170

[0072] Performance Testing The as-coated cutting tools were tested in two parallel cutting tests, Cutting Test 1 and Cutting Test 2, in a longitudinal turning operation on the workpiece material Ovako 825B (100CrMo7-3), a high alloy steel. The cutting speed Vc was 220 m / min, the feed fn was 0.3 mm / rev, the depth of cut was 2 mm, and a water-miscible cutting fluid was used. Machining continued until the end-of-life criterion was reached. One cutting edge per cutting tool was evaluated.

[0073] Tool life criteria are when the first or second flank wear is >0.3mm or the crater area (exposed base material) is >0.2mm 2 The end of life was considered to have been reached when either of these criteria was met. The end of life of the specimen was considered to have been reached. The results of the cutting tests are shown in Tables 8 and 9. TIFF2024519948000013.tif93170TIFF2024519948000014.tif47170

[0074] As can be seen in Table 8, Samples C, D, E, F and G all exhibited high wear resistance. As shown in Table 9, Samples D and E exhibited high resistance to both flank and crater wear in metal cutting of steel and were comparable to the very high performance benchmark, Reference Sample A.

[0075] The cutting tools were also evaluated by exposing them to an abrasive wet blast. The blasting was performed on the rake face of the cutting tool. The blaster slurry consisted of 20 vol% alumina in water and the angle between the rake face of the cutting insert and the direction of the blaster slurry was 90°. The distance between the gun nozzle and the surface of the insert was approximately 145 mm. The pressure of the slurry to the gun was 1.8 bar for all samples and the pressure of the air to the gun was 2.2 bar. The alumina grit was F230 mesh (FEPA42-2:2006). The average time of blasting per area unit was 4.4 seconds. Samples B and C were unable to withstand the wet blasting, the coating of sample B showed significant flaking and sample C showed spot-like flaking. All other samples withstood the wet blasting without destruction of the coating.

[0076] Although the present invention has been described in connection with various exemplary embodiments, it should be understood that the present invention is not limited to the disclosed exemplary embodiments, but on the contrary is intended to encompass various modifications and equivalent arrangements within the scope of the appended claims. Moreover, it should be recognized that any disclosed form or embodiment of the present invention may be incorporated, as a general matter of design choice, into any other disclosed or described or proposed form or embodiment. It is therefore intended to be limited only as indicated by the scope of the appended claims, as attached hereto.

Claims

1. Ti(C,N) layer, Al 2 O 3 and a bond layer therebetween, The Ti(C,N) layer having a thickness of 3 to 25 μm is composed of columnar crystal grains, and the average crystal grain size D of the Ti(C,N) layer 422 is 25-50 nm as measured by X-ray diffraction using CuKα radiation, and the grain size D 422 But the Scherrer formula: Calculated from the full width at half maximum (FWHM) of the (422) peak by 422 is the average grain size of Ti(C,N), K is the shape factor, set here to 0.9, λ is the wavelength of CuKα radiation, set here to 1.5405 Å, B 422 is the FWHM value of the (422) reflection, and θ is the Bragg angle. The Ti(C,N) layer includes a B1 portion adjacent to the bonding layer, and the average grain size of the Ti(C,N) grains in the B1 portion is greater than or equal to the average grain size D 422 and in the B1 portion of the Ti(C,N) layer, the Ti(C,N) grains have an average grain size of 130 to 300 nm as measured by transmission Kikuchi diffraction (TKD) in a plane of the B1 portion of the Ti(C,N) layer extending parallel to the substrate surface.

2. 2. The cutting tool of claim 1, wherein the Ti(C,N) layer in the B1 portion of the Ti(C,N) layer exhibits an orientation as measured by TKD in a plane extending parallel to the substrate surface, with a surface normal of the Ti(C,N) layer parallel to a surface normal of the substrate surface, and ≧93%, preferably ≧95%, of the analyzed area having a <211> direction within 15 degrees of the surface normal of the Ti(C,N) layer.

3. The cutting tool according to claim 1 or 2, wherein the thickness of the B1 portion of the Ti(C,N) layer is 0.5 to 1.5 μm, preferably 0.6 to 0.9 μm, most preferably 0.6 to 0.8 μm.

4. 3. The cutting tool of claim 1 or 2, wherein the bond layer comprises at least one compound selected from the group of titanium carboxylate, titanium oxynitride, and titanium carboxynitride.

5. Grain size D of Ti(C,N) 422 A cutting tool according to claim 1 or 2, wherein the average particle size is 25 to 40 nm, preferably 25 to 35 nm.

6. The Ti(C,N) layer exhibits an X-ray diffraction pattern when measured using CuKα radiation and a θ-2θ scan, where TC(hkl) satisfies the Harris formula: where I(hkl) is the measured intensity (integrated area) of the (hkl) reflection, and I 0 3. A cutting tool according to claim 1 or 2, wherein (hkl) are standard intensities according to ICDD PDF card number 42-1489, n is the number of reflections and the reflections used in the calculation are (111), (200), (220), (311), (331), (420) and (422), and TC(422) is ≧3, preferably ≧4.

7. A 2 O 3 The layer is α-Al 2 O 3 layer, preferably having an average thickness of 1 μm to 15 μm, more preferably 3 to 10 μm. 2 O 3 3. The cutting tool of claim 1 or 2, which is a layer.

8. α-Al 2 O 3 The layer exhibits a texture coefficient TC(hkl), as determined by X-ray diffraction using CuKα radiation and a θ-2θ scan, as defined by the Harris equation, where I(hkl) is the measured intensity (integrated area) of the (hkl) reflection, and I 0 8. Cutting tool according to claim 7, wherein (hkl) are standard intensities according to ICDD PDF Card No. 00-010-0173, n is the number of reflections used in the calculation, and the (hkl) reflections used are (104), (110), (113), (024), (116), (214), (300) and (0012), characterized in that TC(0012) is ≧7.5, preferably ≧7.7, more preferably ≧7.

8.

9. The α-Al 2 O 3 8. The cutting tool according to claim 7, wherein the layer exhibits a Texture Coefficient TC(110) of ≦0.2, preferably ≦0.

1.

10. 3. The cutting tool according to claim 1 or 2, wherein in the B1 portion of the Ti(C,N) layer, the Ti(C,N) grains have an average grain size of 130 nm to 165 nm as measured by TKD in a plane extending parallel to the substrate surface.

11. The α-Al 2 O 3 The layer includes an O1 portion extending 1 μm from the bonding layer, the O1 portion being the α-Al 2 O 3 The layer exhibits orientation as measured by electron backscatter diffraction (EBSD) in cross section, and α-Al 2 O 3 the surface normal of the layer is parallel to the surface normal of the substrate surface, and ≧80%, preferably ≧90%, more preferably ≧95%, and most preferably ≧97% of the analyzed area is α-Al 2 O 3 8. The cutting tool of claim 7, having a <001> orientation within 15 degrees of the surface normal of the layer.

12. Cutting tool according to claim 1 or 2, wherein the Ti(C,N) layer has an average thickness of 4 to 20 μm, preferably 5 to 15 μm.

13. Cutting tool according to claim 1 or 2, wherein the average thickness of the bonding layer is between 0.25 and 2.5 μm, preferably between 0.5 and 2.0 μm.

14. A cutting tool according to claim 1 or 2, wherein the average thickness of the coating is between 5.0 μm and 30.0 μm, preferably between 10 and 20 μm.

15. The cutting tool according to claim 1 or 2, wherein the substrate is a cemented carbide, cermet, or ceramic substrate.